2017
DOI: 10.4238/gmr16039769
|View full text |Cite
|
Sign up to set email alerts
|

Research Article Indices estimated using REML/BLUP and introduction of a super-trait for the selection of progenies in popcorn.

Abstract: ABSTRACT. Selection indices commonly utilize economic weights, which become arbitrary genetic gains. In popcorn, this is even more evident due to the negative correlation between the main characteristics of economic importance -grain yield and popping expansion. As an option in the use of classical biometrics as a selection index, the optimal procedure restricted maximum likelihood/best linear unbiased predictor (REML/BLUP) allows the simultaneous estimation of genetic parameters and the prediction of genotypi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Though conflicting results as to the nature and extent of agronomic correlations are not difficult to find in the literature, our study supported the prevailing notion of moderately positive correlations between ear and yield traits. Likewise, correlations found in this study between expansion volume and agronomic traits were negative, as has been observed multiple times (Brunson, 1937;Dofing et al, 1991;Ziegler and Ashman, 1994;Pereira and Amaral Júnior, 2001;Daros et al, 2002;Li et al, 2002Li et al, , 2007Li et al, , 2008Li et al, , 2009Dhliwayo, 2008). The genetic repeatability estimate for 100-grain weight was found at 0.683, a similar estimate to that found previously (Spaner et al, 1992).…”
Section: Improved Agronomics Of Quality Protein Popcorn Hybridssupporting
confidence: 89%
See 1 more Smart Citation
“…Though conflicting results as to the nature and extent of agronomic correlations are not difficult to find in the literature, our study supported the prevailing notion of moderately positive correlations between ear and yield traits. Likewise, correlations found in this study between expansion volume and agronomic traits were negative, as has been observed multiple times (Brunson, 1937;Dofing et al, 1991;Ziegler and Ashman, 1994;Pereira and Amaral Júnior, 2001;Daros et al, 2002;Li et al, 2002Li et al, , 2007Li et al, , 2008Li et al, , 2009Dhliwayo, 2008). The genetic repeatability estimate for 100-grain weight was found at 0.683, a similar estimate to that found previously (Spaner et al, 1992).…”
Section: Improved Agronomics Of Quality Protein Popcorn Hybridssupporting
confidence: 89%
“…Due to primary selection of popping traits such as expansion volume and popability, popcorn is less optimized than other maize types in multiple agronomic traits such as pest susceptibility, stalk strength, and grain yield, and it has a relatively narrow breeding pool to integrate and improve agronomic traits (Robbins and Ashman, 1984;Sprague and Dudley, 1988;Dofing et al, 1991;Ziegler and Ashman, 1994). Previously, breeders' attempts at introducing dent corn germplasm into popcorn to improve its agronomic fitness have met with little success because of a negative correlation between expansion volume, a key popcorn quality trait, and grain yield (Brunson, 1937;Dofing et al, 1991;Ziegler and Ashman, 1994;Pereira and Amaral Júnior, 2001;Daros et al, 2002;Li et al, 2002Li et al, , 2007Li et al, , 2008Li et al, , 2009Dhliwayo, 2008). However, in 2018, Ren et al (2018) described an interpopulation breeding system between popcorn lines and dent "Quality Protein Maize" (QPM) varieties capable of increasing essential amino acid lysine in the seed proteome to more suitable levels for human dietary needs, and restored popping at early stages in the breeding program.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the positive gains from commercial ear yields, they were low when compared to gains for the same trait obtained by the REML/BLUP methodology (27.32%) ( Table 2). Vittorazzi et al (2017) achieved similar results in genetic gains when applying the REML/BLUP methodology for the analysis of popcorn yield. Furthermore, it can be observed that, for the same index, negative gains resulted for the NER trait when the economic weights used were 1, CV g , CV g /CV e , and h², pointing out to a reduction of the trait, which may be an undesirable factor in advancing the maize breeding program.…”
Section: Resultsmentioning
confidence: 68%
“…Vittorazzi et al. () compared selection with indices, with and without the use of REML/BLUP, and showed superior results using multivariate statistics for the selection of popcorn lines, both for GY and popping expansion.…”
Section: Discussionmentioning
confidence: 99%
“…Nunes, Resende, Santos, and Alves (2017) observed high precision conferred by genotypic values predicted using REML/BLUP when the selection index was compared in Eucalyptus breeding. Vittorazzi et al (2017) compared selection with indices, with and without the use of REML/BLUP, and showed superior results using multivariate statistics for the selection of popcorn lines, both for GY and popping expansion.…”
Section: Discussionmentioning
confidence: 99%